Essential algorithms a practical approach to computer algorithms using Python and C# - Stephens, Rod 1961- (John Wiley & Sons, Inc., 2019)
The revised and updated second edition of Essential Algorithms, offers an accessible introduction to computer algorithms. The book contains a description of important classical algorithms and explains when each is appropriate. The author shows how to analyze algorithms in order to understand their behavior and teaches techniques that the can be used to create new algorithms to meet future needs. The text includes useful algorithms such as: methods for manipulating common data structures, advanced data structures, network algorithms, and numerical algorithms. It also offers a variety of general problem-solving techniques. --
Includes index. - Description based on online resource; title from digital title page (viewed on June 24, 2024)
Keywords: Computer algorithms; Python (Computer program language); C# (Computer program language); Algorithms; Algorithmes; Python (Langage de programmation); C# (Langage de programmation); algorithms; COMPUTERS; Programming; Algorithms; Computers and IT